ECOLA-Based Strategy to Improve Reading Comprehension: Evidence from an Indonesian Senior High School - Sulkifli, Sulkifli (Jurnal Konsepsi, 2025)
This study investigates the effectiveness of the ECOLA (Extending Concept through Language Activities) method in improving reading comprehension among Indonesian senior high school students. The research was conducted through classroom action research at SMA Perguruan Islam Makassar, involving 30 second-grade students over two cycles, each consisting of four meetings. The primary goal was to enhance students' ability to understand both literal and interpretative aspects of reading texts. Quantitative data were gathered using reading comprehension tests, while qualitative data came from classroom observations. The students' average score increased from 36.65 on the diagnostic test to 51.87 in the first cycle and reached 77.08 in the second cycle, indicating significant improvement. Additionally, student engagement improved from 65.83% to 78.76% by the end of the research, reflecting a more active and motivated classroom environment. The ECOLA method encouraged students to connect reading with writing, speaking, and listening, resulting in deeper comprehension and increased participation. The findings demonstrate that ECOLA is an effective instructional strategy for enhancing reading comprehension and student involvement. It is recommended for English as a Foreign Language (EFL) instruction in similar educational settings.